Gestión empresarial y su relación con el sistema de control interno de Molino Samán S.R.L. 2022 - Pacherres Jiménez, Astrild Estephani (2022)
The objective of this study was to investigate the relationship between corporate governance and the internal control system of Molino Samán S.R.L., 2022. A descriptive, explanatory and correlational study with a non-experimental and cross sectional approach was used. The population was the company Molino Samán S.R.L. The sample consisted of 53 employees at the discretion of the researcher, using random procedures. In order to carry out this study, a documentary analysis was carried out in which classification and treatment guidelines were elaborated, and two Likert scale questionnaires were used to evaluate the two variables of the research: business management and internal control system. It was concluded that there is a highly significant relationship between business management and internal control system of Molino Samán S.R.L.2022, having obtained as Pearson's correlation coefficient of 0.871 (significance level was p = 0.000 < 0.01).